Analysis of Marketing Problems in the Apparel Supplier Industry Sector with Analytical Network Process Method - Gur, Seyda; Kaya, Fatma (Fırat University, 2025)
The apparel sub-industry is an industrial area that supports clothing production processes and offers complementary products in production. This industry produces accessories, materials, and auxiliary products required to produce the main components of apparel (garments and textile products). Sub-industry products include complementary products such as fabrics, buttons, zippers, accessories, etc. While the field produces complementary parts of the fashion and textile sector, it also provides support for the main production line of apparel. Marketing strategies in the supply chain are very important in production processes. Factors to be considered in marketing issues can be listed as increasing the efficiency of businesses in the sector, providing a competitive advantage in the market, and maximizing customer satisfaction. The problems affecting the marketing processes of the products of the sub-industry in the apparel sector are changing both the production and distribution stages of the industry to a great extent. The analytical network process method, one of the multi-criteria decision-making methods, was used to analyze the problems encountered in this process. The analysis of these problems and the factors that cause them is of critical importance in order to ensure the efficient operation of the supply chain.

Konfeksiyon yan sanayi, giyim üretim süreçlerine destek veren ve üretimde tamamlayıcı ürünler sunan bir sanayi alanıdır. Bu sanayi, konfeksiyonun ana bileşenlerinin (giysi ve tekstil ürünleri) üretimi için gerekli olan aksesuar, malzeme ve yardımcı ürünler üretmektedir. Yan sanayi ürünleri kumaş, düğme, fermuar, aksesuar vb. tamamlayıcı ürünleri kapsamaktadır. Alan moda ve tekstil sektörünün tamamlayıcı parçalarını üretirken aynı zamanda konfeksiyon ana üretim hattının desteklenmesini de sağlamaktadır. Üretim süreçlerinde tedarik zincirindeki pazarlama stratejileri oldukça önemlidir. Pazarlama konularında dikkate alınması gereken etmenler sektördeki işletmelerin verimliliğini artırmak, pazarda rekabet avantajı sağlamak ve müşteri memnuniyetini üst düzeye çıkarmak şeklinde sıralanabilir. Konfeksiyon sektöründeki yan sanayiye ait ürünlerin pazarlama süreçlerini etkileyen sorunlar endüstrinin hem üretim hem de dağıtım aşamalarını büyük ölçüde değiştirmektir. Bu süreçte karşılaşılan sorunların analizi için çok ölçütlü karar verme yöntemlerinden analitik ağ süreci yöntemi kullanılmıştır. Tedarik zincirinin verimli çalışmasını sağlamak için bu sorunları ve bu sorunlara sebep olan faktörlerin analizi kritik önem taşımaktadır.
Konfeksiyon Yan Sanayi Sektöründeki Pazarlama Sorunlarının Analitik Ağ Süreci Yöntemi ile Analizi
Keywords: Multiple Criteria Decision Making; Çok Ölçütlü Karar Verme